1991
DOI: 10.1071/sr9910025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fire intensity on soil chemistry in a eucalypt forest

Abstract: Soil samples taken in the Wombat State Forest in Victoria, at depths of 0-2, 2-5, and 5-10 cm before and after burning fuel loads of 0 (unburnt control), 15, 50, 150, and 300 t ha-1 were analysed for pH, exchangeable cations and cation exchange capacity, available and total P, organic carbon and soil moisture, over a 2-year, 2000 mm rainfall period. Short term responses (up to 6 months) occurred in levels of exchangeable NH4+, K+, and Mg2+, and long term changes (2 years or longer) over the period of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 25 publications
5
54
2
Order By: Relevance
“…Adams and Boyle [86] reported that a month after a wildfire, available K in the soil of a Quercus rubra-Populus grandidentata forest was significantly higher than pre-fire levels, but the increases were almost gone after a further three months. Tomkins et al [87] found soil K to increase for six months following fire in a Eucalyptus forest. Heavy rainfall one month after the wildfire in the study area may have led to the observed decrease in exchangeable K because of the loss of a high-density-charged fraction such as organic matter, which can lead to K being lost by particulate transport of ash, runoff, or erosion [36].…”
Section: Soil Nutrientsmentioning
confidence: 99%
“…Adams and Boyle [86] reported that a month after a wildfire, available K in the soil of a Quercus rubra-Populus grandidentata forest was significantly higher than pre-fire levels, but the increases were almost gone after a further three months. Tomkins et al [87] found soil K to increase for six months following fire in a Eucalyptus forest. Heavy rainfall one month after the wildfire in the study area may have led to the observed decrease in exchangeable K because of the loss of a high-density-charged fraction such as organic matter, which can lead to K being lost by particulate transport of ash, runoff, or erosion [36].…”
Section: Soil Nutrientsmentioning
confidence: 99%
“…The soil is primarily yellow podsolic soils derived from Ordovician sedimentary rocks and the climate is cool temperate with the majority of the 900-925 mm of annual rainfall in winter and spring. Details on soil chemistry have been published previously (Tomkins et al, 1991).…”
Section: Study Sites and Experimental Designmentioning
confidence: 99%
“…Several studies on the effect of fire on soils have shown changes in soil nutrient levels resulting mainly in total N losses, but short-term increases in available N and other nutrients (Biederbeck et al 1980, Kutiel and Naveh 1987, Fenn et al 1993, Saa et al 1998. Soil chemical properties such as exchangeable Ca++, Mg++ and K+, and pH also increase after fire (Tomkins et al 1991). Microbial biomass is considered an agent of transformation of soil organic materials, and a labile reservoir of nutrients such as N, P, and S (Jenkinson and Ladd 1981).…”
Section: High N Availabilitymentioning
confidence: 99%